Pengaruh bahan ajar fisika terintegrasi konten kecerdasan emosional menggunakan model pembelajaran inkuiri terbimbing terhadap hasil belajar peserta didik kelas X SMAN 13 Padang - yudia laili; Zulhendri Kamus (PILLAR OF PHYSICS EDUCATION, 2019)
Achievement of competence of students in Padang is still 13 SMAN categorized low. This is due to several factors such as the use of learning materials, yet have not integrated the values of character curriculum, assessment of competence 2013 attitudes still are common, and yet there is the attitude of values emotionally developed from material physics. Therefore, this research aims to as an alternative to the solution of the existing problems in improving the competence of learners by using learning materials physics using emotional intelligence content integrated model of learning inkuiri social interactions towards the achievement of the learning results of students of class X SMAN 13 field. The type of research used quasi experimental (quasi experimental research) research design with a randomized control group only design. The population of the research was the entire X-grade learners of SCIENCES listed in the odd semester academic year 2018/2019. The research sample is taken using a purposive sampling technique. Data-collecting instruments in the form of a written post test-test for competence of knowledge and observation sheets for integrated content attitude competency emotional intelligence as well as pieces of performance for the competency skills. Analysis  techniques using description graphs and test the equality of two average.The results showed that the average value of the competency of the experimental class higher from control class for all competencies. From test t, retrieved th > tt so Ho in decline and Hi received, it can be concluded that there is a difference in learning outcomes effects the teaching material integrated content emotional intelligence using a model of learning inkuiry learning achieved learners class X SMAN 13 Padang.